2019
DOI: 10.1002/anie.201902714
|View full text |Cite
|
Sign up to set email alerts
|

DNAzyme‐Loaded Metal–Organic Frameworks (MOFs) for Self‐Sufficient Gene Therapy

Abstract: DNAzymes have been recognized as potent therapeutic agents for gene therapy, while their inefficient intracellular delivery and insufficient cofactor supply precludes their practical biological applications.M etal-organic frameworks (MOFs) have emerged as promising drug carriers without in-depth consideration of their disassembled ingredients.Herein, we report aself-sufficient MOF-based chlorin e6modified DNAzyme (Ce6-DNAzyme) therapeutic nanosystem for combined gene therapyand photodynamic therapy(PDT). The Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
274
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 347 publications
(276 citation statements)
references
References 42 publications
0
274
0
2
Order By: Relevance
“…[20] The extensively utilized DNAzyme relies on Mg 2+ ions,w hose intracellular concentration (0.5 mm) [17] is far below its minimal demand (5 mm) [16] for sustaining efficient DNAzyme biocatalysis.Thus various metal [21] and metallic oxides [22] have been introduced, as endogenous stimuli-responsive nanocarriers,t os upply DNAzyme cofactors. [23] Nevertheless,t he nonenzymatic,a utocatalytic,D NAzyme machinery is rarely integrated with multimodal imaging platforms.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The extensively utilized DNAzyme relies on Mg 2+ ions,w hose intracellular concentration (0.5 mm) [17] is far below its minimal demand (5 mm) [16] for sustaining efficient DNAzyme biocatalysis.Thus various metal [21] and metallic oxides [22] have been introduced, as endogenous stimuli-responsive nanocarriers,t os upply DNAzyme cofactors. [23] Nevertheless,t he nonenzymatic,a utocatalytic,D NAzyme machinery is rarely integrated with multimodal imaging platforms.…”
Section: Introductionmentioning
confidence: 99%
“…However,i ti sn ot possible to distinguish between contributions from cobalt ferrite and ferrihydrite to these peaks,since both compounds include octahedrally and tetrahedrally coordinated Fe III . [19] Besides,t he delivery of their cargo payloads usually rely on the passive accumulation to at arget site. [2b, 18] Over the past years,M OFs have been used for drug delivery applications,s ince they are able to accommodate therapeutic agents in their structure.H owever,t heir potential as gene carriers has been rarely investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[2b, 18] Over the past years,M OFs have been used for drug delivery applications,s ince they are able to accommodate therapeutic agents in their structure.H owever,t heir potential as gene carriers has been rarely investigated. [19] Besides,t he delivery of their cargo payloads usually rely on the passive accumulation to at arget site. [19b] To this end, we have demonstrated the feasibility of gene delivery using magnetically responsive Fe@ZIF-67-based microtransporters.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Additionally, controllable enzymes release can be achieved because of the acid-sensitive nature of ZIF-8. [17] In further studies, researchers found that the surface charge of proteins limited the applicability of biomimetic mineralization approach. In light of this problem, a convenient and versatile amino-acid-boosted biomimetic strategy was developed to realize the encapsulation of different proteins and even nanoparticles within a MOFs by our group.…”
Section: In Situ Encapsulationmentioning
confidence: 99%